Enhancing learning outcomes in violin music education: a systematic review - Shao, Jinyi (Frontiers in Education, 2026)
The violin has long been a prominent instrument in music education, but challenges remain in sustaining student interest and optimizing learning efficacy. This systematic review explores effective educational strategies that can enhance student interest and performance in violin learning. After searching relevant databases, 19 articles were identified, of which 9 met the study’s inclusion criteria. This review identifies several gaps in current violin teaching practices, including the predominance of traditional teacher-centered instruction and the limited effectiveness of learning outcomes. To address these gaps, the studies included in this review highlight a range of innovative strategies, such as teaching-equipment innovations, personalized learning methods, and motivational techniques. Findings suggest that combining traditional and modern teaching methods can significantly improve learning outcomes. This review summarizes recommendations for educators to enhance their teaching methods and foster a more engaging and effective learning model for violin learners.Systematic review registrationhttps://osf.io/8eahv.